Transition Management Using a Market Transformation Approach: Lessons for Theory, Research, and Practice from the Case of Low-Carbon Housing Refurbishment in the UK. (October 2013) - Killip, Gavin
Work on target-led transitions has highlighted the interdependence between 'niche' and 'regime' actors in steering change towards strategic goals. Similarly, market transformation (MT) has a long history in product markets, improving the energy efficiency of stocks of energy-using appliances through research, minimum standards, energy labels, incentives, procurement, competitions, and stakeholder networks. Attempts to apply MT to buildings have failed to fully take account of the differences between appliance markets and the multiple markets which frame energy use in buildings. The case of refurbishment of UK housing is considered here, for which there is a system of different markets in operation. MT principles are considered in relation to the sources and diffusion of innovation in project-based industries; the management of different expectations among innovators and incumbents; technical risks associated with doing low-carbon refurbishment work; and the role of policy in simultaneously stimulating supply and demand. An iterative process with feedback loops and coordination is proposed to link training, standard-setting, and compliance checks. No institutional infrastructure exists for such an enterprise, which would need to cross established boundaries between regime actors. The case of UK housing refurbishment throws up lessons for theory, research, and practice which could be developed through further case studies.